SPECTRAL MANIFESTATIONS OF IMPURITY ATOMS DIFFUSION IN CRYOGENIC INERT GAS MATRICES - B. P. Nevzorov (Вестник Кемеровского государственного университета, 2015)
The paper analyzes the reasons for the change of the vibrational spectrum of matrix-isolated substances. It is shown that one of the reasons for the spectrum change is the filling of space in the real crystal lattice by impurity atoms. Impurity atoms complete the crystal lattice of inert gas to a pseudocrystal, which is reflected in the Raman spectra. Another reason for the spectral parameters change of the impurity bands observed upon annealing argon matrix is caused by its restructuring and activation of diffusion processes with the formation of molecules associate impurities.